Evaluation of pain and patient satisfaction by music therapy in patients with endoscopy/colonoscopy - Bashiri, Mehrnoosh; Akçalı, Didem; Coşkun, Demet; Cindoruk, Mehmet; Dikmen, Asiye; Uçaner Çifdalöz, Burçin (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Endoscopy and colonoscopy are frequently performed procedures to evaluate the gastrointestinal system. These procedures are sometimes disturbing and painful for the patient. In gastrointestinal suits, endoscopy and colonoscopy may be performed on awake or sedated patients. Music therapy is a common and non-pharmacological treatment for various medical conditions, pain, and anxiety. The aim of the present study was to add music therapy to sedation administered during endoscopy and colonoscopy. The effect of music treatment on drug consumption, anxiety, and pain was investigated. Materials and Methods: American Anesthesiologist Association I-III adult patients scheduled for endo/colonoscopy were randomized to music treatment and no music treatment groups. Patients with endoscopic ultrasound and endoscopic retrograde colangiopancreaticography were excluded from the study. Anxiety score and pain severity were evaluated before and after the procedure. Heart rate, mean arterial pressure, and oxygen saturation were recorded before, during, and after the procedure. Total drug consumption was recorded. Patient satisfaction and desire for the same protocol for recurrent procedures were investigated. Results: Music therapy added to deep sedation administered by anesthesiologists provided decreased anxiety score and propofol consumption. Patient satisfaction was increased, and patients reported a desire for the same protocol for recurrent procedures. Conclusion: The present study may serve as the beginning of using music therapy for pain treatment in gastroenterology procedures in our hospital with/without sedation. Music and other non-pharmacological treatment methods are on the way to be also considered in pediatric patients. Cite this article as: Bashiri M, Akçalı D, Coşkun D, Cindoruk M, Dikmen A, Uçaner Çifdalöz B. Evaluation of pain and patient satisfaction by music therapy in patients with endoscopy/colonoscopy. Turk J Gastroenterol 2018; 29: 574-9.